Pengaruh Struktur Aset, Volatilitas Laba, dan Fleksibilitas Keuangan Terhadap Struktur Modal: Studi Kasus pada Perusahaan Manufaktur Sektor Barang Konsumsi yang Terdaftar di BEI Periode Tahun 2021-2023 - Shintia Ivana Ayu Lianawati; Tri Purwani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to analyze the influence of assets structure, earning volatility, and financial flexibility of apital structure in the manufacturing companies within the consumer goods sub-sector subsector. The sample for this research consists of 62 companies listed on the Indonesia Stock Exchange (BEI) to submit their financial reports for the 2021-2023 period. The data used in this research is secondary data and the sample was selected using a purposive sampling method. The analytical tool used is multiple linear regression analysis.The results of hypothesis testing show that assets structure, earning volatility has an on capital structure, while financial flexibility have no effect on financial performance